A FINANCIAL EVALUATION OF WHEAT PRODUCTION PROJECTS UNDER CENTER PIVOT IRRIGATION SYSTEMS IN ANBAR GOVERNORATE - Ghazi, N. S.,; D. S. Barbaz, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The research aims to identify the financial feasibility of cultivating the wheat crop under modern irrigation systems in desert areas and to clarify the impact of the capacity of the systems in those projects in achieving the financial feasibility of their establishment, using the economic evaluation criteria for the projects. The research included a study of 60 projects in Anbar Governorate for the 2020-2021 production season. It has been shown that projects that use several systems, despite their high investment costs, can recover the money invested in them within a relatively short period. The projects that use modern irrigation systems covering 60 donums were among the best projects that achieved technical efficiency in the productivity of the wheat crop, and the average net income reached the cash in the sample is about 1.3 billion dinars, while the average net income per donum in the research sample is about 189 thousand dinars. The sample was not able to achieve accounting profits, The research recommended the need to use electric power systems as an alternative to relying on electric power generators, as the average price of solar power systems in the Iraqi market is currently within reach.